Calculations of hyperpolarizability and two-photon absorption cross sections of organic charge-transfer compounds - Mahmoudi, Shiva (My University)
YÜK-TRANSFER ORGANİK BİLEŞİKLERDE HİPERPOLARİZASYON VE İKİ-FOTON SOĞURMA TESİR KESİT HESAPLAMALARI Fizikteki en önemli konulardan biri, maddenin ışıkla etkileşimi ve bu etkileşimden kaynaklanan geçişlerdir. Kuantum mekaniği açısından, bu etkileşim, genellikle soğurulma gibi farklı süreçlere yol açabilecek bir geçişi tetikler. Bu soğurulma süreci genellikle taban halinden daha yüksek bir elektronik hale doğru gerçekleşir. Işık yoğunluğu ve malzeme özellikleri ile ilgili olarak, doğrusal ve doğrusal olmayan soğurulma süreçleri vardır. Çoğu malzemelerde doğrusal soğurma süreci gerçekleşir. Ancak, bazı malzemeler, gelen ışığa doğrusal olmayan bir yanıt gösterir. İki foton soğurma (TPA) süreci, üçüncü mertebeden doğrusal olmayan bir süreçtir. Bu süreç, düşük enerjili görünür veya yakın kızılötesi ışıkla yüksek enerjili elektronik hallerin uyarılması ile gerçekleşir. İki fotonun “aynı anda” soğrulması sonucu TPA gerçekleşir ve bu, iki fotonun ardışık soğurulmasından farklıdır. TPA, tek foton spektroskopisini tamamlayıcı bir teknik olarak, moleküler elektronik yapı hakkında bilgi edinmek için kullanılabilir. Uygulamalı alanda, iki foton litografi, veri depolama, hücre görüntüleme ve tıbbi konularda, biyolojik dokulara daha iyi nüfuz etme özelliği sayesinde, kullanılabilir. Vücut dokusu düşük enerjili ışığa yarı saydam olduğundan, büyük TPA kesiti olan moleküllerle işaretlenmiş tümörlere enerji taşınması mümkündür. Büyük TPA kesitine sahip organik sistemler genellikle X-B-Y yapısına sahiptir, B, X ve Y fragmentlerini bağlayan, elektron akseptör (A) veya elektron donörleri (D) köprüsüdür. Bu tezde, sülfür atomunu bir köprü olarak kullanıp donör ve akseptör parçalarını bağladığımız dört farklı küçük molekül için TPA kesitlerini hesapladık.

CALCULATIONS OF HYPERPOLARIZABILITY AND TWO-PHOTON ABSORPTION CROSS SECTIONS OF ORGANIC CHARGE-TRANSFER COMPOUNDS One of the most important topics in physics is the study of matter and its interaction with light. Quantum mechanically speaking, due to this interaction, a transition happens which may lead to different phenomena such as absorption. This absorption process usually occurs from the ground state to a higher electronic state. Regarding the intensity of the light and properties of the materials, there are linear and nonlinear absorption processes. Linear absorption occurs in most materials. However, certain materials show a nonlinear response to the incident light. The two-photon absorption is a third order nonlinear process. This process can populate highly energetic electronic states by irradiating them with low-energy visible or near-infrared light. TPA happens when two photons are absorbed simultaneously, which makes it different from the sequential absorption of two photons. TPA can be used to gain information on molecular electronic structure as a complementary technique to one-photon spectroscopy. Practical applications have already been established in two-photon lithography, data storage, cell imaging, and medicine because of its enhanced ability to penetrate biological tissue. Since body tissue is semi-transparent to low-energy light, the delivery of energy through the body to targets such as tumors labeled by molecules with a large two-photon absorption (TPA) cross section would be possible. Organic systems with large TPA cross-sections often have the structure X-B-Y, with B being a bridge connecting fragments X and Y, electron acceptors (A) or electron donors (D). In this thesis, we report our calculated TPA cross sections for four small molecules with the sulfur atom as a bridge to link donor and acceptor moieties.
Yük-transfer organik bileşiklerde hiperpolarizasyon ve iki-foton soğurma tesir kesit hesaplamaları
Keywords: Fizik; Hiperpolarizabilite; Hyperpolarizability; Iki-foton soğurma; Lineer olmayan optik; Non-linear optics; Physics; Two-photon absorption